Menjaga Kesehatan Mental Pada Usia Remaja - Muhamad Daffa R; Baradheta Herlambang; Novalyta Putri R; Kamila Mutiara T (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Mental health in adolescence is an important aspect that influences an individual's emotional, social and intellectual development. At this stage, teenagers face various challenges, such as physical changes, social pressure, and the search for self-identity, which can affect their mental well-being. Maintaining teenagers' mental health is very important to prevent future psychological problems, such as depression, anxiety and stress disorders. Strategies that can be implemented to maintain mental health in teenagers include forming positive habits, open communication with family and friends, and activities that support balance between body and mind, such as exercise and meditation. Apart from that, support from parents, schools and the community in creating a supportive environment also plays an important role in strengthening teenagers' mental resilience. This research aims to provide a deeper understanding of the importance of maintaining mental health in adolescents and identify effective steps in preventive and intervention efforts to support their mental well-being.